IMPLEMENTASI PELAYANAN PRIMA PADA NASABAH BANK SYARIAH MANDIRI CABANG BENGKALIS - Rahim Rahim; Dwi Astuti; Teguh Widodo (Inovbiz: Jurnal Inovasi Bisnis, 2016)
Abstract: The present research was conducted atBank Syariah Mandiri of Bengkalis Branch. The purposes of this research are to know the implementation of  the  excellent  service  for  Bank  Syariah  Mandiriof  Bengkalis  Branch’s customer, and to know what kind of services that have been implemented for their customer. The kind of research isthe description research.The result of the research  showed  thatis  the  Bank Syariah  Mandiri  of  Bengkalis  Branchhave implemented the excellent service to the customer according the standards that assigned by Bank Syariah Mandiri of Bengkalis Branch. Keywords: Service Excellent, Customer, Bank